Giant Faraday rotation in single- and multilayer graphene - Crassee, Iris; Levallois, Julien; Walter, Andrew L.; Ostler, Markus; Bostwick, Aaron; Rotenberg, Eli; Seyller, Thomas; van der Marel, Dirk; Kuzmenko, Alexey B. (Nature physics, 2011)
The rotation of polarized light in certain materials when subject to a magnetic field is known as the Faraday effect. Remarkably, just one atomic layer of graphene exhibits Faraday rotations that would only be measurable in other materials many hundreds of micrometres thick. The rotation of the polarization of light after passing a medium in a magnetic field, discovered by Faraday 1 , is an optical analogue of the Hall effect, which combines sensitivity to the carrier type with access to a broad energy range. Up to now the thinnest structures showing the Faraday rotation were several-nanometre-thick two-dimensional electron gases 2 . As the rotation angle is proportional to the distance travelled by the light, an intriguing issue is the scale of this effect in two-dimensional atomic crystals or films—the ultimately thin objects in condensed matter physics. Here we demonstrate that a single atomic layer of carbon—graphene—turns the polarization by several degrees in modest magnetic fields. Such a strong rotation is due to the resonances originating from the cyclotron effect in the classical regime and the inter-Landau-level transitions in the quantum regime. Combined with the possibility of ambipolar doping 3 , this opens pathways to use graphene in fast tunable ultrathin infrared magneto-optical devices.